(untitled) (Global Journal of Human-Social Science, 2013)
Lizhuang the first town of the Yangtze River during the Anti-Japanese War together with Chengdu Chongqing Kunming was listed as one of the rear four big resistance cultural centers The overseas mail could reach as long as it was written Lizhuang China In the special time Lizhuang a town with the original population of less than ten thousand played a special role in the Chinese history This paper mainly discusses the cross-cultural communication effect of Lizhuang China during the period of Anti-Japanese War